STRATEGI MISI DI CHINA ABAD 16 DALAM TULISAN MATTEO RICCI - Aluisius Pramudya Daniswara (Jurnal Teologi (Journal of Theology), 2016)
De Christina Expeditione apud Sinas, which was translated into China in the Sixteenth Century: The Journals of Matthew Ricci 1583-1610, is one of Riccis most important manuscripts since it reveals how Matthew Ricci accomplished his mission in China. Matthew Ricci was a man from the West, which at the time was entering the age of Renaissancea modern era marked by significant cultural, scientific and economic growths. He then utilized the components of Renaissance Humanism culture to break through Chinese people. From there, Ricci was able to move beyond the administrative and geographic boundaries, either physically or culturally, from one country to another country. Learning from Riccis manuscript, it is clear that today a conquest model of mission can only do disservice, especially if the Church wants to proclaim the kingdom of God, which is full of love, peace, and communion. It may cause suspicion or denouncement of the Church service. It is therefore of paramount importance for the Church to remember her basic duty, which is to proclaim the Good News of the love of God in Jesus Christ. Consequently, the Church must become a community which manifests the sacrament of the Divine wherever she may be.